2011
DOI: 10.2308/accr.00000005
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Nonfinancial Disclosure and the Cost of Equity Capital: The Initiation of Corporate Social Responsibility Reporting

Abstract: We examine a potential benefit associated with the initiation of voluntary disclosure of corporate social responsibility (CSR) activities: a reduction in firms’ cost of equity capital. We find that firms with a high cost of equity capital in the previous year tend to initiate disclosure of CSR activities in the current year and that initiating firms with superior social responsibility performance enjoy a subsequent reduction in the cost of equity capital. Further, initiating firms with superior social responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
1,069
4
19

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,695 publications
(1,150 citation statements)
references
References 60 publications
58
1,069
4
19
Order By: Relevance
“…Secondly, firms with superior CSR performance are likely to disclose their CSR activities through sustainability reports (Dhaliwal et al, 2011) and also are likely to allow confirmation of such reports by third parties. As a result, CSR reporting increases the transparency and credibility of information, leads to a sound internal control system, reduces information asymmetry and reduces financial constraints.…”
Section: ⅱ Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Secondly, firms with superior CSR performance are likely to disclose their CSR activities through sustainability reports (Dhaliwal et al, 2011) and also are likely to allow confirmation of such reports by third parties. As a result, CSR reporting increases the transparency and credibility of information, leads to a sound internal control system, reduces information asymmetry and reduces financial constraints.…”
Section: ⅱ Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Current Earning (LABA) is measured by net income before extraordinary item divided by average total assets (Holbrook, 2010;Dhaliwal et al, 2011).…”
Section: Persistent Earningsmentioning
confidence: 99%
“…Two of the studies were by Dhaliwal and co-authors. Dhaliwal, et al (2011) reported their findings that "firms with a high cost of capital in the previous year tend to initiate disclosure of CSR activities in the current year and that initiating firms with superior social responsibility performance enjoy a subsequent reduction in the cost of equity capital. Further, initiating firms with superior social responsibility performance attract dedicated institutional investors and analyst coverage.…”
Section: Empirical: Correlates Of Csr Reportingmentioning
confidence: 99%